HUBUNGAN TINGKAT PENGETAHUAN TENTANG REKAM MEDIS DENGAN KELENGKAPAN PENGISIAN CATATAN KEPERAWATAN PADA INSTALASI RAWAT INAP DI RUMAH SAKIT AT-TUROTS AL ISLAMY SLEMAN - Sri Utami; Amalina Tri Susilani; Fahmi Hakam (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2016)
Abstract : in the law of the republic of Indonesia Number 44 Year 2009, hospital is a comprehensive personal service institution that provide health service for impatients, outpatients, and emergency patients. One of the quality indicators of health service in the hospital is the medical record service. In Permenkes Decree No. 269 / Menkes / PER/ III/2008, Article 1, paragraph 1 states that, medical record is explained as files contain all notes and health services that has been received by patient. To observe the relation between nurses’ knowledge level of medical record and how comprehensive they fill the nursing documentation. This study used observational analysis with cross sectional approach. Subjects in this study were all nurses in At-Turots Al-Islamy public hospital, Sleman. The study objects were impatients medical record files that were analyzed with saturated sample technique. The study was conducted from April to May 2016 with questionnaire as study instrument. The obtained data then analyzed with bivariate an univariate analysis, where chisquare equation was used in bivariate analysis. The study showed the value of nurses’ knowledge was 23,07% (sufficient), and the comprehensiveness of nursing documentation in At-Taurots Al-Islamy public hospital, Sleman.